Saj’ Murashsha’ dalam Surah Al-Waqi’ah: (Studi Analisis Balaghah) - Raudhatul Jannah; Ariza Amalia; Nabila Nashfati; Harun Al-Rasyid (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article examines saj’ in the science of badi’ and provides examples of the use of saj’ murashsha’ in Surah Al-Waqi’ah. Saj’ is a part of muhassinat al-lafdziyah that specifically discusses the similarity of the final letters in two or more fashilahs. Saj’ is divided into three types: saj’ mutharraf, saj’ murashsha’, and saj’ mutawazi. This research employs a qualitative approach through library study. Based on the analysis conducted by the researcher, there are six instances of saj’ murashsha’ found in Surah Al-Waqi’ah.